Save our soles SG : SOS SG - Khoo, Qi Ying Shan (2017)
Save Our Soles SG (SOS SG) was a campaign aimed at empowering women with the knowledge and awareness of the short term and long term health consequences of wearing high heels, and what they could do to care for their feet. Four final-year students of the Wee Kim Wee School of Communication and Information at the Nanyang Technological University conceptualised, planned, and ran this campaign, with the hopes of motivating more women to save their soles.